Business and IT Alignment - Majstorović, Milosav N. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Over the last two decades, the need for alignment of business needs and opportunities of information technology (IT) has been considered  one of the key issues in IT management. Research in the field of the alignment of business and IT gained momentum in the last decade of the last century when it was realized that the cost-effectiveness of IT investments directly contributed to the so-called strategic alignment, ie. alignment between business strategy and IT strategy. It is recognized that IT changes the direction in which companies organize their business processes, communication with customers and deliver their products and services. The aim of this study is to investigate the current situation in solving the problem of alignment of business and IT in order to allow a comparison of different definitions and a conceptualization of this phenomenon, and also to consider the efforts made so far in order to solve this problem. The conceptualization of the phenomenon of alignment of business and IT is given through the strategic alignment model that had the biggest impact in this area. The question of the applicability of the model and the framework developed for the purpose of alignment stems from the challenges facing the problem of alignment of business and IT. These challenges are categorized and particularly elaborated in this paper. Introduction The annual survey of the Society for Information Management (www.simnet.org), ranked "Business and IT alignment," among the top ten concerns of higher management in the period from 2003 - 2010. In the academic literature, alignment is conceptualized in different directions. One, perhaps a dominant direction, advocates the principle that IT must at least be organized and managed in such a way that it reflects business management. There are different formal and informal definitions of alignment. A wider definition regards the alignment of business and IT as a degree to which IT applications, infrastructure and organization allow and shape business strategy and processes, as well as the process itself, i.e. as activities or methodologies for achieving a certain degree of alignment. For studying this complex problem, it is important to make its conceptualization through the development of appropriate models. The SAM (Strategic Alignment Model) model had the biggest impact in this domain and it will be mainly discussed here. Alignment models Initially, IT had a strictly auxiliary function in a business system and it belonged to the department for assistance. However, advances in technology made many realize the potential of new IT in execution and strategic functions. In literature, there are many formal and informal definitions of the phenomenon of alignment. Informal definitions provide an intuitive meaning of alignment and support communication and understanding among business participants; however, due to their imprecision, they are less helpful in articulating what exactly makes a good alignment, and how it could be measured. Formal definitions are based on conceptualization, i.e. developed models for the phenomenon of alignment. The first developed model which had a big impact is the strategic alignment model (SAM). This model describes the alignment of business and IT through two dimensions: strategic fit and functional integration. Together with these dimensions, the model defines four fundamental domains: business strategy, information technology strategy, organizational infrastructure and processes, and infrastructure and information technology processes. Although very important, the model itself has undergone some criticism, especially in the context that the concept of the SAM model does not reflect the reality of current management practices of real business. In order to overcome this problem, there have been developed models and frameworks that present an empirical elaboration of the alignment problem. In this context, the most cited and applied empirical model is the strategic alignment maturity model. This model defines six criteria (i.e. variables) for measuring the maturity of alignment: communication, measurement values, governance, partnership, scope and architecture. Efforts to overcome business and IT alignment and the effects of these efforts Measurement of the IT and IT investment contribution has been an area of intensive research for decades. The research results show that this issue is an open problem for IT management and business in general. The specific IT investments can have positive effects on the organization A, but not on the organization B, depending on how IT is used. So, synergistic effects of IT and other organizational factors must be considered as well. Despite the conceptualization and operationalization of the alignment, the alignment of business and IT remains a challenge for many organizations. The most important challenges of the alignment of business and IT that follow from empirical studies are: -     the problem of the lack of a generally accepted framework or model; -     descriptive and prescriptive alignment models; -     limited feature alignment measurements; -     alignment requires a comprehensive approach; -     the problem of lack of knowledge and lack of definition of business; -     dynamic reality; -     evolutionary role of IT. Conclusion For a long time, the alignment between business and IT has been attracting the attention of the academic community as well as of companies that want to become and remain competitive. This work has contributed to a more precise definition of the concept of alignment. It presented its conceptualization and defined the problems and challenges that stand in the way to successful implementation of the alignment of business and IT. In order to seek solutions that will alleviate the problem of the alignment of business and IT, the following approaches are to be researched and applied: -     Enterprise architecture as a way of a comprehensive and unique modeling of an organization, its business operations and IT. -     Formal modeling of the organization business processes and their implementation, analysis, monitoring and upgrading using the system for business process management. These approaches are expected to enable the continuous management of the problem of business and IT alignment.
Keywords: Alignment; IT strategy; Business strategy; Strategic alignment model